2019
DOI: 10.3390/ijerph16234698
|View full text |Cite
|
Sign up to set email alerts
|

Parent Engagement and Support, Physical Activity, and Academic Performance (PESPAAP): A Proposed Theoretical Model

Abstract: An emerging area of research within public health is the interaction between parents and their children for the promotion of physical activity. Higher levels of daily physical activity may not only improve physical health but also yield better academic performance by improving cognitive skills, classroom behavior, and academic achievement within the pediatric population. However, no theoretical model has yet been proposed to interrelate constructs of parental engagement and support, physical activity, and acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Respondents claimed that there are "lots of parent volunteers" (education leader) and "it's a very young community so good parent involvement; never any shortage of coaches" (health leader). Parent engagement improves participation opportunities, and includes volunteering during physical activity opportunities or providing transportation [13]. Higher levels of childhood physical activity lead to continual parent engagement which further facilitates positive physical activity behaviors [13].…”
Section: Key Resultsmentioning
confidence: 99%
“…Respondents claimed that there are "lots of parent volunteers" (education leader) and "it's a very young community so good parent involvement; never any shortage of coaches" (health leader). Parent engagement improves participation opportunities, and includes volunteering during physical activity opportunities or providing transportation [13]. Higher levels of childhood physical activity lead to continual parent engagement which further facilitates positive physical activity behaviors [13].…”
Section: Key Resultsmentioning
confidence: 99%
“…Sakamaki et al (2022) Students who engage in appropriate cognitive processes can learn better, impacting academic success. Burns et al (2019) and Wheaton et al (2016) A positive relationship was found between behavioral engagement and attendance and academic and extracurricular performance. High concentration in educational activities characterizes academically strong students, evidenced by higher course grades.…”
Section: Student Engagement and Academic Performancementioning
confidence: 89%
“…Involved students will be more motivated and willing to interact with the subject content (Condliffe et al, 2017;Eckardt et al, 2020). A positive relationship was f ound between behavior engagement, academic performance (Burns, Bai, Fu, Pfledderer, & Brusseau, 2019) attendance (Wheaton, Chapman, & Croft, 2016), and extracurricular activities. High involvement in academic act ivities is a characteristic of academically strong students, as evidenced by higher subject grades.…”
Section: Student Engagement and Academic Performancementioning
confidence: 91%
“…Parental support for physical activity and sport is needed for healthy child development and success within the sport environment [ 25 , 26 ]. However, perceived parental discrimination may increase psychological distress and thus lower support for child participation in various out-of-school activities.…”
Section: Introductionmentioning
confidence: 99%